Estudo da concentração de material particulado em ambientes internos e externos de bibliotecas - Santos, Raissa Aparecida Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Our twenty-first century society and the rhythm of life and work we have to face in our daily routine compel us to spend most of our lifetime in closed environments, in our houses, educational institutions, hospitals, airports, amongst as many others. The study of the air quality in internal environments (IAQ) is very important for monitoring people’s health effects and their environmental comfort in these locations. One essential parameter to analyze this measure is to evaluate the concentration of dispersed particulates in the air, specially focusing on those thinner particles (below the diameter of 2,5 μm), they can pose serious risks for human being because they can remain in the lungs, penetrate through the pores of our skin, amongst other harmful effects on human’s health. In this work the air quality inside the public library Profª Josina Vasques Ferrari and at Unesp public state library was evaluated, both located in Itapeva, as well as a third one, inside the Communitarian Library of the Federal University in Carlos (UFSCar) from march to may in 2012. In those environments it was analyzed if the concentration of particulates pose any real treat to the users. The equipment used for particle sampling in real time was DataRam 4 (Model DR 4000). The results given for those concentrations of particulates in both internal and external environments revealed figures within the safe standard established by the WHO (World Health Organization), from 25 to μg/m³, the only exception occurred on the fifth floor of the UFSCar library, where the average for concentration stayed at 25,30 of μg/m³

A sociedade do século vinte e um e o ritmo de vida e trabalho aos qual estamos submetidos nos obriga a passar a maior parte do dia em ambientes fechados, seja em nossas residências, instituições de ensino, hospitais, aeroportos, dentre outros. O estudo da qualidade do ar em ambientes internos (QAI) é de suma importância para se medir e controlar o bem estar e conforto ambiental de seus ocupantes. Um dos parâmetros essenciais de análise da QAI é avaliar a concentração de material particulado dispersos no ar com atenção às partículas finas (abaixo de 2,5 μm de diâmetro), essas apresentam maior incidência de riscos à saúde humana, uma vez que podem se alojar nos pulmões, penetrar nos poros da pele, dentre outros efeitos prejudiciais ao homem. Este trabalho objetivou avaliar a qualidade do ar na biblioteca pública municipal Profª Josina Vasques Ferrari e na biblioteca da Unesp, ambas em Itapeva; além da biblioteca comunitária da Universidade Federal de São Carlos (UFSCar) entre os meses de março e maio de 2012. Foram coletados dados para verificar se a concentração de material particulado naqueles ambientes oferecia riscos aos usuários. O equipamento utilizado para amostragem de partículas em tempo real foi o DataRam 4 (Modelo DR 4000). As médias obtidas daquelas concentrações nos ambientes internos e externos apresentaram valores dentro do limite proposto pela OMS (Organização Mundial de Saúde), fixado em 25 μg/m³, com exceção do quinto piso da biblioteca comunitária da UFSCar, onde a concentração média de partículas ficou em 25,30 μg/m³
Keywords: Ar - Poluição - Medição; Poluição do ar de interiores - Aspectos da saúde; Poluentes; Ar - Poluição - Normas; Ar - Qualidade; Saude ambiental; Bibliotecas; Indoor air pollution